1998
DOI: 10.1002/(sici)1099-1700(199801)14:1<31::aid-smi754>3.0.co;2-b
|View full text |Cite
|
Sign up to set email alerts
|

Stress and contingency management in the treatment of irritable bowel syndrome

Abstract: Ninety patients with irritable bowel syndrome (IBS) who did not respond to medical treatment were randomly assigned to four treatment conditions—two experimental groups: stress management and contingency management; and two control groups: medical treatment and placebo. The subjects underwent 12 individual sessions which were specific for each condition. All the subjects completed symptom‐monitoring diaries. Thirty‐three dropped out during the assessment or treatment. The subjects who received training in cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
1

Year Published

2002
2002
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 28 publications
0
14
0
1
Order By: Relevance
“…Four of these were identified since the previous monograph. (234,238,242,243) None of the trials were considered to be at low risk of bias.…”
Section: Quality Of Evidence: Very Lowmentioning
confidence: 99%
“…Four of these were identified since the previous monograph. (234,238,242,243) None of the trials were considered to be at low risk of bias.…”
Section: Quality Of Evidence: Very Lowmentioning
confidence: 99%
“…More recently, since van Dulmen, Fennis, & Bleijenberg's (1996) RCT involving a group form of CBT, sample sizes have been noticeably larger with Toner, Segal, and colleagues (1998), Fernandez, Perez, Amigo, & Linares, (1998), and Boyce, Talley, Truman, Balsam, & Nandurkar (2001, all having over 20 patients per condition. Impressively, Drossman, Toner, Whitehead, and colleagues' (2003) RCT had over 400 participants distributed across four conditions.…”
Section: Cognitive and Behavioral Therapiesmentioning
confidence: 99%
“…On the other hand, when CBT has been compared to a psychologically active attention placebo condition (Blanchard et al, 1992, Study 1 and Study 2; Payne & Blanchard, 1995;Toner, Segal, et al, 1998;Fernandez et al, 1998;Boyce et al, 2001;Tkachuk, Graff, Martin, & Bernstein, 2003;Drossman et al, 2003), the results are mixed. Blanchard et al's (1992) two studies found no advantage for CBT over a combination of alpha suppression biofeedback and pseudo medication; nor did Toner and colleagues find any difference between CBT and a psychoeducational support group; nor did Boyce and colleagues (2001) find a difference between CBT and relaxation (or between CBT and enhanced routine medical care).…”
Section: Cognitive and Behavioral Therapiesmentioning
confidence: 99%
“…In einer Reihe von Studien wurden insbesondere kognitiv-behaviorale bzw. verhaltenstherapeutische Therapieprogramme, die teilweise mit Entspannungsverfahren wie Biofeedback oder progressive Muskelrelaxation kombiniert wurden, überprüft (Blanchard et al 1992;Fernandez et al 1998;Greene u. Blanchard 1994;Payne u. Blanchard 1995;Schwarz et al 1990;Shaw et al 1991;van Dulmen et al 1996). Ebenso zeigte sich eine Kombination aus Verhaltenstherapie und Pharmakotherapie einer reinen Pharmakotherapie kurz-und langfristig überlegen (Heymann- Monnikes et al 2000).…”
Section: Psychotherapeutische Verfahrenunclassified